Safe electrophysiologic profile of the neprilysin-inhibitor sacubitril in combination with different antiarrhythmic drugs. (3rd October 2022) - Frommeyer, G; Mengel, C; Wolfes, J; Eckardt, L; Ellermann, C
Abstract: Background: Observational clinical data suggest a direct effect of sacubitril on cardiac electrophysiology. However, data concerning the impact of combination of sacubitril with antiarrhythmic drug therapy is sparse. Purpose: We aimed at characterizing the electrophysiologic effects of a combination therapy of sacubitril with the class III-drug sotalol and the class IB-agent mexiletine in a sensitive, experimental whole-heart model. Methods and results: 25 isolated rabbit hearts were retrogradely perfused. Hearts were treated with mexiletine (25 μM, 13 hearts) or sotalol (100 μM, 12 hearts) after generating baseline data. Eight endo- and epicardial monophasic action potentials and ECG recordings demonstrated an abbreviation of action potential duration (APD90, −21 ms, p<0.01) and no significant changes of QT interval (+10ms, p=ns) after administration of mexiletine. Spatial dispersion of repolarization (SDR) remained stable after mexiletine treatment (+6 ms, p=ns) whereas effective refractory periods (ERP) were significantly prolonged (+80 ms, p<0.01). Sotalol prolonged cardiac repolarization (APD90: +1 ms, p=ns; QT: +24 ms, p<0.01) and amplified spatial dispersion (+19 ms, p<0.01) without changing ERP (+8 ms, p=ns). Additional treatment with sacubitril (5 μM) led to a significant reduction of APD90 (−12 ms, p<0.01), QT interval (−20 ms, p<0.01) and ERP (−23 ms, p<0.01) in the presence of a stable SDR (−4 ms, p=ns) in the mexiletine group. In the sotalol group, additional administration of sacubitril abbreviated APD90 (−9 ms, p<0.05) and QT interval (−13 ms, p<0.01) and reduced ERP (−18 ms, p<0.01) without affecting SDR (−3 ms, p=ns). Ventricular vulnerability was assessed by a predefined pacing protocol employing premature extra stimuli and burst stimulation. After lowering the potassium concentration, 30 episodes of torsade de pointes tachycardia were observed after sotalol treatment (vs. 0 episodes under baseline, p<0.05). Additional sacubitril treatment significantly suppressed torsade de pointes tachycardia (8 episodes, p<0.05) in the sotalol-group. No proarrhythmic effect was observed after mexiletine treatment (8 episodes vs. 3 episodes under baseline conditions, p=ns). Additional sacubitril treatment did not increase ventricular vulnerability (32 episods, p=ns). Conclusion: Sacubitril in combination with antiarrhythmic drugs demonstrates a safe electrophysiologic profile. In class IB- and class III-pretreated hearts, sacubitril abbreviates cardiac repolarization duration and effective refractory periods without changing spatial dispersion of repolarization. Thereby, sacubitril reduces the occurrence of torsade de pointes-tachycardia in antiarrhythmic pretreated hearts. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Deutsche Stiftung für Herzforschung (to G.F.)